Interactive Nutrition Education Is More Effective in Terms of Improved Levels of Glycated Hemoglobin in Adolescent Patients with Poorly Controlled Type 1 Diabetes – A Randomized Study - Dłużniak-Gołaska, Karolina (Diabetes Metab Syndr Obes, 2019)
INTRODUCTION: Effectively conducted nutrition education is one of the key elements of the therapy of type 1 diabetes. The aim of the study was to compare the effectiveness of two methods of nutrition education. MATERIAL AND METHODS: A noninvasive interventional randomized single-blind study included 151 patients (13.7±2.2 years old) with poorly controlled type 1 diabetes, treated with the use of insulin pumps. The participants were randomly divided into two groups: a control group (C) in which informative education methods were used (a lecture) and an experimental group (E) in which interactive methods (quiz and multimedia application) were additionally applied. The concentration of glycated hemoglobin (HbA1c) was the primary outcome. The secondary outcomes were: standard deviation score-body mass index (SDS-BMI), standard deviation score-systolic blood pressure (SDS-SBP), standard deviation score-diastolic blood pressure (SDS-DBP), scores of Nutrition Knowledge Survey (NKS) and indices of healthy and unhealthy diet. RESULTS: A marked reduction in HbA1c concentrations was observed after 3 months in group E [−0.47% (−0.77; −0.17), P<0.01; P=0.038 for the intergroup difference]. The positive effect was no longer present after 6 months. No significant changes regarding HbA1c were noted in group C at any stage of the study. After 6 months, both groups obtained better results in one part of NKS (“Blood glucose response to food”): group C [0.41 (0.15; 0.66), P<0.01], group E [0.80 (0.52; 1.08), P<0.001; P=0.042 for the intergroup difference]. No statistically significant differences between groups were noted as regards the remaining parameters. CONCLUSION: Interactive nutrition education is more effective in terms of improved levels of HbA1c in children and adolescents with poorly controlled diabetes. However, an intensification of training frequency is recommended due to the transient effect of education.